Comparison of the inhibitory capacity of two groups of pure natural extract on the crystallization of two types of material compound urinary stones in vitro study. Issue 1 (October 2015) - Beghalia, Mohamed; Ghalem, Said; Allali, Hocine
Abstract: Urolithiasis is defined as the result of an abnormal precipitation within the urinary tract. This precipitation is most often from the normal constituents of the urine. This is a fairly common condition in the population. She is happy and recurrent etiology is often unknown if hypothetical. In Algeria, as in many countries, a large number of patients use herbal medicines in the treatment of their diseases including urolithiasis. Thus the aim of this study is the most widely used to evaluate the effectiveness of aqueous extracts of medicinal plants, in the treatment of calcium urolithiasis oxalo-and magnesium-amoniaco in vitro. The study also examines the effect of these extracts on the states of crystallization (nucleation, crystal growth, crystal aggregation), followed by photography on polarized light microscope.In this regard, we are devoted to studying the crystallization steps from oxalo-calcium and phospho-calcic prepared as artificial urine and supersaturated aqueous solutions, maintained at 37 °C to remain close to biological conditions. Extracts of the first group of herbs: Ammodaucus leucotrichus, Ajuga iva, Globularia alypum, Atriplex halimus are studied on the crystallization calcium oxalate, we cite the Ammodaucus leucotrichus which acts on the stages of nucleation, growth and the aggregation with a total inhibition. The second group of extracts plants tested on calcium phosphate crystallization : Acacia raddiana, Citrullus colocynthis, Rhus tripartita, Pistacia lentiscu, Warionia saharae, are able to significantly reduce phosphate crystallization in vitro. It is easily proved by FTIR and optical microscope. In conclusion the results of our work allows us to confirm the use of these plants as an aqueous decoction, in the field of urolithiasis. These activities may help to strengthen the body in depressed situations.